2017
DOI: 10.1063/1.4991858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave annealing on electrical characteristics of TiN/Al/TiN/HfO2/Si MOS capacitors

Abstract: In this letter, microwave annealing over a wide range of power (300–2700 W) in nitrogen ambient was performed on TiN/Al/TiN/HfO2/Si metal-oxide-semiconductor capacitors. Capacitors with rapid thermal annealing at 500 °C were also fabricated for comparison at the same wafer temperature measured during microwave annealing at 2700 W. For microwave annealed capacitors, key parameters such as equivalent oxide thickness, interface state density, oxide trapped charge, leakage current density, and breakdown voltage we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The breakdown electric field strength is comparable to other reports about HfO2. 29,30 There are a few possible electron transport mechanisms including direct tunneling, Poole-Frenkel (P-F) emission, Fowler-Nordheim (F-N) tunneling, and Schottky emission, etc.…”
Section: Gate Leakagementioning
confidence: 99%
“…The breakdown electric field strength is comparable to other reports about HfO2. 29,30 There are a few possible electron transport mechanisms including direct tunneling, Poole-Frenkel (P-F) emission, Fowler-Nordheim (F-N) tunneling, and Schottky emission, etc.…”
Section: Gate Leakagementioning
confidence: 99%
“…The effects of MW plasma treatment on exposed materials/substrates require intricate evaluations, since electrical and thermal conductivity play an outstanding role during processing. In this sense, conductive materials can be annealed through excitation of electron mobility by exposure to microwaves even without plasma ignition [19,20] and the dissipation of thermal energy is thus clue.…”
Section: Introductionmentioning
confidence: 99%
“…The effects are ascribed to the details of microwave absorption, which selectively affects Si-H bonds, and thus hydrogen bonds were restructured [31]. Some studies have reported microwave annealing in the thin-film coating technology [32][33][34][35]. The MWA has two major microwave heating processes: ohmic conduction and dielectric polarization losses, mainly influenced by the thickness and conductivity of the thin films; and the other is the dielectric permittivity of the thin film materials [36].…”
Section: Introductionmentioning
confidence: 99%